The interplay of poverty and employment trajectories in couples around the transition to parenthood in Germany - Christina Siegert (Deutsches Institut für Wirtschaftsforschung (DIW), 2025)
The transition to parenthood is a critical period that exacerbates gendered economic inequality, with mothers more likely than their partners to experience employment disruptions and income losses. This study examines individual poverty risk among partnered indivduals (N=1,237) in Germany from a life course perspective, analyzing how gendered career patterns around first births between 1992 and 2013 intersect with changes in individual poverty risk, i.e. under the assumption of no income pooling. Applying multichannel sequence analysis (MCSA) to data from the Socio-Economic Panel, the findings reveal substantial heterogeneity in how poverty- employment trajectories unfold after childbirth, both between genders and among women. Men's employment and financial stability remain largely unchanged after parenthood, whereas women's economic trajectories vary widely. While most women are financially stable before childbirth, their post-birth pathways diverge. Some return to work quickly with minimal poverty risk, while others take extended parental leave and face prolonged risks. A smaller group is persistently vulnerable even before childbirth, with consistently weak labor market attachment. Over time, the share of women in financially stable trajectories has increased, likely reflecting policy changes that support earlier labor market reintegration. However, a subset of women remains at high risk, particularly those with lower pre-birth earnings. The findings highlight the necessity of long observation periods, as poverty risks evolve beyond the initial years of parenthood, and demonstrate the utility of MCSA in describing these dynamics.
Keywords: 330; poverty; employment; childbirth; motherhood; life course; sequence analysis